Green Synthesis of Zinc Oxide Nanoparticles via Dennettia tripetala Extracts: Optimization, Characterization, and Biological Activity Evaluation - Omolara Olusola Oluwaniyi; Blessing Tarhe Oyewo (Nano Select)
ABSTRACT This study examined the synthesis of zinc oxide nanoparticles (ZnONPs) with ethanolic extract from leaf and fruit of Dennettia tripetala (Class: Annonaceae) and the assessment of their biological activities. Mixing of Zn (C2H3O2)2.2H2O solution and the ethanolic extracts resulted in color change, indicating the formation of ZnONPs. pH, temperature, and concentration of metal ions were varied to optimize the amount of nanoparticles formed. Ultraviolet‐visible (UV‐Vis) spectroscopy gave a surface plasmon resonance (SPR) peak at 356 nm (DTL‐ZnONPs) and 367 nm (DTF‐ZnONPs), confirming the presence of the synthesized ZnONPs. The scanning electron microscopy (SEM) shows aggregation of spherical and rod‐like shaped nanoparticles. x‐Ray diffraction (XRD) analysis is crystalline in nature with an average crystallite size of 17.17 ((DTL‐ZnONPs) and 12.90 (DTF‐ZnONPs) nm. FT‐IR analysis showed O─H, C═O, N─H, and C─C stretching and aliphatic vibrations of hydrocarbon chains of the synthesized ZnONPs. The ZnONPs gave the maximum zone of inhibition of 18.07 (DTL‐ZnONP) and 17.14 mm (DTF‐ZnONP). Antioxidant activity carried out using DPPH radical scavenging gave an IC50 value of 227.18 (DTL‐ZnONP) and 201.21 (DTF‐ZnONP) µg/mL. Moreover, the cytotoxic effect of ZnONPs is in a concentration‐dependent manner. Therefore, this work showed that ZnONPs are good potential therapeutic agents for treating microbial infection, oxidative stress, and other pertinent disease.